Innovation, co-creation, and design thinking : how Salesforce's Ignite team accelerates enterprise digital transformation - Beckman, Sara Lynn; Whalen, Elizabeth (London : The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business, 2018)
This case follows the evolution of the Ignite team at Salesforce, the cloud computing Customer Relationship Management (CRM) company. Launched in 1999 to serve enterprise customers with a Software as a Service (SaaS) application, Salesforce today is one of the most highly valued cloud computing companies with a market capitalization of over $90B. Its core offerings surround its CRM service and include the Commerce Cloud, Sales Cloud, Service Cloud, Data Cloud, Marketing Cloud, and Analytics Cloud. The story follows the process and evolution of the ignite team formed to penetrate further into the large-scale enterprise market.
Originally Published InBeckman, S., & Whalen, E. (2018). Innovation, co-creation, and design thinking: How Salesforce's Ignite team accelerates enterprise digital transformation. The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Salesforce; Cloud computing -- Data processing -- Case studies; Web services -- Case studies; Computer software industry -- United States -- Case studies